Demographic Profile, Clinical Features, Imaging, and Outcomes in Patients with Traumatic Brain Injury Presenting in Garhwal Himalayas in Tertiary Care Hospital - Garg, Ritish; Arora, Pankaj; Shankar, Vibhu (Indian Journal of Neurotrauma, 2024)
Introduction Traumatic brain injury (TBI) poses a significant global health challenge, accounting for over 50% of trauma-related deaths and emerging as a leading cause of mortality and disability.Objective This article studies the demographic characteristics, clinical features, imaging findings, and outcomes of TBI patients.Materials and Methods This was a retrospective observational study conducted on 490 patients with TBI. Data regarding age, gender, socioeconomic status, and residential location were extracted from medical records. Neuroimaging reports, including computed tomography (CT) scans results, were analyzed for structural and functional insights.Results The majority of TBI cases involved individuals aged 21 to 40, with a higher incidence in males. Road traffic accidents were identified as the most common mode of injury, followed by falls. Most of the patients had moderate Glasgow Coma Scale scores at admission. CT scans indicated skull fractures, cerebral edema, and subdural hematomas as common findings. Most patients did not require ventilator support, and the majority had a hospital stay of less than 10 days. At discharge, 89.8% exhibited favorable outcomes, while 4.3% experienced mortality during treatment. Follow-up data demonstrated an overall mortality rate of 8.8%, with 89.2% achieving complete recovery within a month.Conclusion The study underscores the importance of understanding the multifaceted aspects of TBI, emphasizing the need for integrated approaches in tertiary medical care to optimize patient outcomes and contribute to effective public health strategies.
Keywords: traumatic brain injury; demographic profile; clinical profile; outcome